Prevalence and characteristics of sleep problems of Indonesian children in 0 – 36 months old - Giwang Yayi Retnosari; Irwanto Irwanto; Lilik Herawati (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2021)
Background: A quarter of child population experiences sleep problems in their first three years of life. Inadequacy and problems of sleep for children may be caused by various causes that impact their mental health, emotional states, physical states, and immune systems. This also may culminate to behavioural problems. Objective: The aim of this study is to identify the prevalence of sleep problems in 0–36 months old Indonesian children. Methods: A cross-sectional study was conducted in Tulungagung, East Java, Indonesia. Children aged 0–36 months old were enrolled by using a quota sampling. Brief Infant Sleep Questionnaire (BISQ) was used in this study to assess the sleep problems. All obtained data were presented as a distribution and percentage of each variable referring to the BISQ indicators. Results: A total of 493 children were enrolled in this study. This study found that there were 153 children (31%) who had experienced sleep problems, 79 children (16%) who had nocturnal sleep duration less than 9 hours, 62 children (12,8%) who had nocturnal waking more than 3 times, and 20 children (4%) who had duration of wakefulness during the night more than 1 hour respectively.Conclusion: Although majority of parents thought that there were no sleeping problems with their children, the prevalence of sleep problems in 0–36 months old Indonesian children was quite high (31%), suggesting low parental awareness towards sleep problems of their children.